A note on Köthe–Toeplitz duals and multiplier spaces of sequence spaces involving bicomplex numbers - Değirmen, Nilay; Sağır, Birsen (Journal of applied analysis, 2024)
In this paper, we generalize the notions of the Köthe–Toeplitz duals of sequence spaces by introducing the concepts of bicomplex α-dual, bicomplex β-dual and bicomplex γ-dual, and also we compute them for some bicomplex sequence spaces for , and . Furthermore, we define a concept of bicomplex multiplier space as the bicomplex version of multiplier space of two sequence spaces and support this definition with examples.